Wear Performance Optimization of Silicon Nitride (Si3N4)-Hexagonal Boron Nitride (hBN) Composite Using Genetic Algorithm (GA) - Sachin, Ghalme; Ankush, Mankar; Yogesh, Bhalerao (Recent Patents on Materials Science, 2017)
Background: Research in the field of orthopedics is trying to evaluate the materials for an artificial joint with minimum wear volume loss, so as to extend the life. Various material combinations are proposed to overcome this issue. Silicon nitride (Si3N4) is non-oxide ceramic suggested as a new alternative for hip/knee joint. Objective: In this paper, an attempt has been made to evaluate the optimum proportion of load and % volume of hexagonal boron nitride (hBN) in Si3N4 to minimize wear volume loss (WVL). Method: From a thorough review of literature in the field of biomaterials, several patents of application of silicon nitride as the alternative material for hip/knee joint replacement are identified and discussed herewith. To determine the wear performance of Si3N4-hBN, the experiments were conducted according to Design of Experiments (DoE) 128;“ Taguchi method and a mathematical model is developed. Further, this model is processed with GA to find out the optimum percentage of hBN in Si3N4 to minimize wear volume loss against steel (ASTM 316L) counterface. Results: Taguchi method presents 15N load and 12% volume of hBN to minimize WVL of Si3N4. GA optimization offers 18.452N load and 8.46% volume of hBN to minimize WVL in Si3N4.
Keywords: silicon nitride (Si3N4)